Characteristics and components of self-management interventions for improving quality of life in cancer survivors: A Systematic Review - Rimmer, Ben; Brown, Morven C.; Sotire, Tumi; Beyer, Fiona; Bolnykh, Iakov; Balla, Michelle; Richmond, Catherine; Dutton, Lizzie; Williams, Sophie; Araújo-Soares, Vera; Finch, Tracy; Gallagher, Pamela; et al. (Cancers, 2024)
Self-management can improve clinical and psychosocial outcomes in cancer survivors. Which intervention characteristics and components are beneficial is unclear, hindering implementation into practice. We systematically searched six databases from inception to 17 November 2021 for studies evaluating self-management interventions for adult cancer survivors post-treatment. Independent reviewers screened for eligibility. Data extraction included population and study characteristics, intervention characteristics (TIDieR) and components (PRISMS), (associations with) quality of life (QoL), self-efficacy, and economic outcomes. Study quality was appraised, and narrative synthesis was conducted. We identified 53 papers reporting 32 interventions. Studies had varying quality. They were most often randomised controlled trials (n = 20), targeted at survivors of breast (n = 10), prostate (n = 7), or mixed cancers (n = 11). Intervention characteristics (e.g., provider, location) varied considerably. On average, five (range 1-10) self-management components were delivered, mostly “Information about condition and its management” (n = 26). Twenty-two studies reported significant QoL improvements (6 also reported significant self-efficacy improvements); these were associated most consistently with combined individual and group delivery. Economic evaluations were limited and inconclusive. Self-management interventions showed promise for improving QoL, but study quality was variable, with substantial heterogeneity in intervention characteristics and components. By identifying what to adapt from existing interventions, these findings can inform development and implementation of self-management interventions in cancer.
Online veröffentlicht: 19. Dezember 2023
Gesehen am 25.02.2025